(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2010)
This case report is of a 50yrs old man who got admitted in BIRDEM Hospital in a state of unconsciousness for 5 hours .He is a known case of hypertension and diabetes mellitus for the last 12 years and was on insulin. Hypoglycemia was detected, treated with intravenous glucose and the patient regained consciousness. On further query he complained of repeated episodes of nausea, palpitation and sweating for the last 12 years. The episodes were initially labeled as hypoglycemia but blood sugar was never found in hypoglycemic range. The patient was on multiple antihypertensive medications but blood pressure was uncontrolled. All the investigations were normal including 24hrs urinary VMA, serum adrenalin and noradrenalin except ultrasonography of whole abdomen which showed a mass measuring 72x 76 mm in left suprarenal region. One night the patient again developed palpitation, chest discomfort, severe headache and profuse sweating. Blood pressure was recorded 240/160 mmHg. Blood sample was drawn for adrenalin, noradrenalin, 24hrs urine collection was done for VMA and was found very high. The patient was diagnosed as having left adrenal pheochromocytoma. After controlling blood pressure and other preoperative preparations left adrenalectomy was done. Histopathology revealed phaeochromocytoma. Per and postoperative periods were quite eventful. Blood pressure was normal without any antihypertensive drug during discharge. The patient was discharged with the advice to come for follow up after 1 month. DOI: 10.3329/jbcps.v28i2.5371 J Bangladesh Coll Phys Surg 2010; 28: 113-116